EKSISTENSI PANDONGANI PERSPEKTIF HUKUM ISLAM DAN HUKUM ADAT - Adi Gunawan Harahap; Sawaluddin Siregar; Zulfan Efendi Hasibuan (Yayasan Baitul Hikmah al-Zain, 2024)
Pandongani is the best man and bridesmaid at traditional Batak weddings. Pandongani has been around for a long time, and the existence of pandongani to accompany the bride and groom is generally known by the Batak traditional community. This research wants to examine the existence of pandongani in the study of Islamic law and customary law. This research method uses empirical juridical methods. In Islamic law there is no problem with the practice of pandongani. And according to Batak customary law, Pandongani are required to be present to accompany Batak traditional wedding ceremonies.